2015
DOI: 10.1063/1.4917254
|View full text |Cite
|
Sign up to set email alerts
|

Improved photoluminescence characteristics of order-disorder AlGaInP quantum wells at room and elevated temperatures

Abstract: Photoluminescence decay dynamics in an InGaN/GaN/AlGaN single quantum wellA set of nominally undoped CuPt-B type ordered (Al x Ga 1Àx ) 0.5 In 0.5 P quantum-wells with disordered (Al 0.7 Ga 0.3 ) 0.5 In 0.5 P barriers were grown and characterized using transmission electron microscopy and photoluminescence spectroscopy. Such structures are potentially beneficial for light emitting devices due to the possibility of greater carrier confinement, reduced scattering into the indirect valleys, and band-offset adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Atomic ordering in ternary or quaternary semiconductors has been proven to have a dramatic effect on electronic band structure [ 109 , 110 , 111 ]. Several studies have theoretically and experimentally shown the difference of the physical properties between ordered and disordered structures such as InGaAs, GaAsSb, InGaP [ 112 ], AlInP [ 113 ] and AlGaInP [ 114 ] Previously, the use of scanning tunneling microscopy (STM) to identify atomic ordering has been reported [ 115 ]. Conventional HRTEM imaging associated with diffraction pattern methods also can provide information about the atomic ordering [ 116 , 117 , 118 , 119 , 120 ].…”
Section: Atomic Orderingmentioning
confidence: 99%
“…Atomic ordering in ternary or quaternary semiconductors has been proven to have a dramatic effect on electronic band structure [ 109 , 110 , 111 ]. Several studies have theoretically and experimentally shown the difference of the physical properties between ordered and disordered structures such as InGaAs, GaAsSb, InGaP [ 112 ], AlInP [ 113 ] and AlGaInP [ 114 ] Previously, the use of scanning tunneling microscopy (STM) to identify atomic ordering has been reported [ 115 ]. Conventional HRTEM imaging associated with diffraction pattern methods also can provide information about the atomic ordering [ 116 , 117 , 118 , 119 , 120 ].…”
Section: Atomic Orderingmentioning
confidence: 99%
“…22,27 Recent time-resolved and continuous-wave photoluminescence measurements from similarly designed quantum-well samples grown in the same MOCVD chamber also showed a doubling in at room temperature with no reduction in emission intensity as the GaInP growth temperature was reduced from 750 °C (disordered) to 650 °C (ordered). 19 As there was no change in the CL intensity between 725 °C and 675 °C in this study, we interpreted this as a doubling of without much impact from a relatively longer . This would lead to a doubling in ≈ but only a slight decrease in the quantum efficiency that is proportional to ( + ) ⁄ and is close to 0.9-1 for both growth temperatures.…”
Section: A Luminescence Away From Dislocationsmentioning
confidence: 99%
“…The integrated CL intensities from the samples grown at 725 °C and 675 °C are very similar, in line with previous photoluminescence results with dislocation-free order/disorder quantum wells. 19 However, further reduction of the growth temperature of the quantum well to 625 °C results in a decline in CL intensity of 30%.…”
Section: A Luminescence Away From Dislocationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Периодические структуры таких включений могут об-разовывать сверхрешетки, состоящие из квантовых ям, проводов или точек. Явления спонтанного возникнове-ния наноструктур создают основу для новой технологии получения упорядоченных массивов неоднородностей -базу для опто-и микроэлектроники нового поколе-ния [1][2][3].…”
Section: Introductionunclassified